2015
DOI: 10.1002/pds.3758
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the possible association between montelukast and neuropsychiatric events among children with asthma: a matched nested case‐control study

Abstract: These data did not detect a consistent significant positive association between montelukast and NE in children with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 41 publications
1
39
0
4
Order By: Relevance
“…In 2009, the US Food and Drug Administration mandated a label change for montelukast and other leukotriene receptor antagonists to include neuropsychiatric adverse events (e.g., depression and suicidality) as a precaution (FDA, 2017). Nonetheless, Ali could not establish a significant association between montelukast and neuropsychiatric events in children with asthma (Ali et al 2015).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In 2009, the US Food and Drug Administration mandated a label change for montelukast and other leukotriene receptor antagonists to include neuropsychiatric adverse events (e.g., depression and suicidality) as a precaution (FDA, 2017). Nonetheless, Ali could not establish a significant association between montelukast and neuropsychiatric events in children with asthma (Ali et al 2015).…”
Section: Discussionmentioning
confidence: 83%
“…Nonetheless, Ali could not establish a significant association between montelukast and neuropsychiatric events in children with asthma (Ali et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-three studies, including two non-English studies [12,25], were selected for a narrative review. The study types include cohort studies (n = 2) [21,23], nested case-control studies (n = 2) [22,24], pharmacovigilance studies (n = 10) [4][5][6][7][8][9][10][11][12][13], ITS analysis (n = 2) [26,27], case series (n = 1) [28], case reports (n = 6) [29][30][31][32][33][34], review of case reports (n = 1) [25], and conference abstracts (n = 9) [35][36][37][38][39][40][41][42][43]. Of the included articles, twelve studies reported suicidal conditions as one of the outcomes [6, 10, 11, 21-23, 25, 26, 32, 36, 37, 40].…”
Section: Search Resultsmentioning
confidence: 99%
“…Observational studies could complement the findings of RCTs since they have greater generalisability and longer follow-up time. With the concerns about the neuropsychiatric safety of LTMAs, some observational and pharmacovigilance studies were conducted to examine this association [4][5][6][7][8][9][10][11][12][13][21][22][23][24]. This review aims to systematically evaluate the evidence from the published literature of different study designs to investigate the association between NEs and LTMAs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ali et al examinated this association among children with asthma and 1920 subjects less than 18 years of age with a primary diagnosis of asthma between 1 January 1998 and 31 December 2009 were identified. A clear dose-response relationship was not observed, with an adjusted OR of 1.01 (95 % CI [0.88, 1.14] for experiencing NE [123, 124]. …”
Section: Introductionmentioning
confidence: 99%